TRANSPORT SÛR ET DURABLE : UNE NOUVELLE APPROCHE DES PARTIES PRENANTES POUR LE MANAGEMENT DU TSD Partie 2 : Le mode d‘emploi - M. Said Kammas; M. Sohaib Zendal (European Scientific Journal, ESJ, 2014)
This communication aims to present an innovative reflection on the stakeholder theory and safe and sustainable transport (SST). In particular, it is to examine the significance of this recent approach for the management of SST system. This reflection is indeed the subject of increasing attention in managerial practices and lies at the heart of debates that address the problem of SST. It encompasses a set of proposals that suggest that all stakeholders should be put at the heart of SST in a partnership approach and collaboration. The article will introduce a new way of thinking about optimal governance, there by driving the SST strategy in a participatory and responsible logic. Among the deliverables to propose at the end of this article:  Identify all stakeholders involved in the SST ;  Presentation of the classification scale stakeholders in the SST ;  Presentation of roles and responsibilities of STAKEHOLDER and their impact on road safety;  Presentation of a battery SST actions in different places by different STAKEHOLDERS  Exposure of an array of information and actions between the STAKEHOLDERS in the SST